Activation and block of the adult muscle-type nicotinic receptor by physostigmine: single-channel studies - Militante, Julius (2008)
The plant-derived acetylcholinesterase inhibitor physostigmine has previously been shown to act on the nicotinic acetylcholine receptor (nAChR) causing either direct activation or potentiation of currents elicited by low concentrations of nicotinic agonists, or, at higher concentrations, channel block. We examined mouse adult-type muscle nAChR activation by physostigmine and found that channel activation by physostigmine exhibits many characteristics common with channel activity elicited by nicotinic agonists. Single-channel conductance was indistinguishable, and mutants known to slow channel closing in the presence of nicotinic agonists had a similar effect in the presence of physostigmine. However, physostigmine is a very inefficacious agonist. The presence of physostigmine did not alter the effective opening rate for a subsaturating dosage of carbachol, suggesting that physostigmine does not interact with the nicotinic agonist binding site. Mutations to a residue (αK125) previously identified as part of the putative binding site for physostigmine reduced the duration of openings elicited by physostigmine but the effects were generally small and, in most cases, non-significant. At higher concentrations, physostigmine blocked channel activity. Block manifested as a reduction in the mean open time and the emergence of a closed state with a mean duration of 3-7 ms. The properties of block were consistent with two equivalent blocking sites per receptor with microscopic binding and unbinding rate constants for physostigmine of 20 μM(-1)s(-1) and 450 s(-1) (K(D) 23 μM). These observations indicate that physostigmine is able to activate muscle nAChR by interacting with a site other than the nicotinic ligand-binding site.